Pengantar dan Pengenalan Konsep Dasar Algoritma Pemrograman - Selviana Anggreani; Yahfizham Yahfizham (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
An introduction to algorithms starts from the basic concepts of algorithms. An algorithm is a series of organized steps to solve a problem, taking into account systematic sequence and logical goals. Meanwhile, a programming algorithm is a combination of instructions that a computer must carry out when solving a problem. Mastering good programming algorithms is absolutely necessary for those who want to master computer science or mathematics. For this reason, this article aims to help understand algorithms through basic concepts through literature methods from various existing sources so that we can also discuss their history, characteristics and properties, algorithm structure, notation including naturalness, pseudocode, and flowcharts.